Tantangan dan Transformasi: Perjalanan Evolusi Pemasaran Menuju Era Global (Studi Kasus pada Toko Galeri Ulos Sianipar di Kota Medan) - Suhairi; Anisyah Risky Nasution; Nabila Prahaski; Yulia Anggraini (Universitas Muhammadiyah Surabaya, 2023)
Abstract This study describes the journey of the Ulos Sianipar Gallery in facing challenges and transformations in marketing Ulos fabric products globally. Using qualitative interview methods, this research explores the marketing strategies implemented, the obstacles faced, and the adaptations made by this store in facing global market dynamics. The results of interviews with the owner, manager and staff of the Ulos Sianipar Gallery revealed that this shop has used effective marketing strategies, including the use of social media and local partnerships, to promote Ulos fabric widely. However, interviews also identified challenges such as market competition and distribution difficulties that affected their efforts. The discussion highlights the adaptations and innovations made by this store to respond to changing global market preferences. This research shows the complexity and importance of adaptation and innovation in marketing products with cultural backgrounds to an ever-changing global market. In conclusion, an in-depth understanding of the challenges, successful marketing strategies and adaptations required by the Ulos Sianipar Gallery provides valuable insight for other businesses seeking to market local cultural products to a competitive global market. This study also underlines the importance of flexibility and a deep understanding of global markets in promoting and preserving cultural heritage in the current era of globalization. Keywords: Ulos Cloth, Global Marketing, Global Marketing Strategy.